Delivery Methods Preferred by Targeted Extension Clientele for Receiving Specific Information - John G. Richardson; R. David Mustian (Journal of Applied Communications, 1994)
Results from this study of extension clientele in North Carolina depict the need for Extension professionals to provide educational opportunities through multiple program delivery methods.